The effect of western juniper on the estrous cycle in beef cattle. (February 2015) - Welch, Kevin D.; Stonecipher, Clint A.; Gardner, Dale R.; Panter, Kip E.; Parsons, Cory; Deboodt, Tim; Johnson, Bryan
Highlights: Bark and needles from western juniper trees can be abortifacient to cattle. Western juniper bark does not affect estrus in cattle. Western juniper bark does not affect conception rates in cattle. Abstract: Numerous evergreen trees and shrubs contain labdane acids, including isocupressic acid, which can cause late-term abortions in cattle. Recent research has shown that the bark from western juniper trees can also cause late-term abortions in cattle. Additionally, ranchers have observed that cattle in western juniper-infested rangelands tend to have decreased conception rates. The objective of this study was to determine if western juniper alters the estrous cycle of cattle. Fourteen heifers (10 treated and 4 control) were monitored for 74 days for signs of normal estrous behavior, with a 21 day feeding trial with western juniper bark from days 28–48, after which the cattle were bred naturally with a bull. The cattle were checked for pregnancy 30 days after all cattle had been bred. The data from this study indicate that exposure to western juniper bark does not affect normal estrus, estrous cycle or conception rates of cattle.